2020
DOI: 10.11646/phytotaxa.447.1.4
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Three new combinations in <em>Gloeocantharellus</em> (Gomphales, Agaricomycetes) from Mexico based on molecular evidence</strong></p>

Abstract: In this study, we included for the first time three Mexican Gomphaceae species in a molecular phylogeny. These species were described as members of the genus Gomphus, despite their tropical and subtropical habitat. We undertook a molecular analysis using the atp6 and SSU mitochondrial loci and nuclear ribosomal LSU. Our analysis showed that the three species studied are better included as members of Gloeocantharellus. In this study, we are suggesting three new combinations: Gloeocantharellus albidocarneus, G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…This classification is consistent with some previous studies [ 1 , 3 ]. Our phylogenetic analysis supports a sister relationship between Gomphus and Turbinellus , contrasting with those studies in which Turbinellus , together with two or more genera of Gomphaceae, were found to be sisters to either Gomphus alone or Gomphus together with several species of Ramaria [ 2 , 63 , 64 , 65 ]. The previous definition of gomphoid fungi [ 1 ], including Gloeocantharellus , turned out to be unnatural.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This classification is consistent with some previous studies [ 1 , 3 ]. Our phylogenetic analysis supports a sister relationship between Gomphus and Turbinellus , contrasting with those studies in which Turbinellus , together with two or more genera of Gomphaceae, were found to be sisters to either Gomphus alone or Gomphus together with several species of Ramaria [ 2 , 63 , 64 , 65 ]. The previous definition of gomphoid fungi [ 1 ], including Gloeocantharellus , turned out to be unnatural.…”
Section: Discussioncontrasting
confidence: 99%
“…Gomphus harbors conspicuous members of Gomphaceae and are often confused with other genera in the family. Recent analyses [ 3 , 63 , 64 , 65 ] indicated that Gomphus, in its broader sense, constitutes a paraphyletic group of fungi with Ramaria sensu lato. To maintain the monophyly of Gomphus , some species were transferred to Gloeocantharellus , and Turbinellus was resurrected [ 1 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research aimed to clarify the diversity and identity of European species of this hypogeous or semi-hypogeous genus. Considering the related literature, it can be observed that among the scattered polyphyletic clades of Ramaria , various morphologies of basidiomata are present, such as resupinate-odontoid ( Kavinia , Ramaricium ), agaricoid stipitate ( Gloeocantharellus ), pileate ( Gomphus , Turbinellus ), club-shaped ( Clavariadelphus ), pileate and also ramarioid ( Phaeoclavulina ) ( Humpert et al 2001 , Giachini et al 2010 , Wannathes et al 2018 , González-Ávila et al 2020 ). The monophyly of the genus Ramaria is not supported in multigene analyses and the morphology of the coralloid sporocarp is suggested to be the ancestral one of the Gomphales , while the other types (resupinate, club-shaped, pileate and sequestrate) are its derivatives ( Humpert et al 2001 , Giachini et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Gautieria forms a monophyletic clade with its closely related sister group Ramaria subg. Ramaria ( Humpert et al 2001 , Giachini et al 2010 , González-Ávila et al 2020 ). The assessment of the taxa belonging to Gomphales and the relevance of the unification under the name Ramaria for some clades and Gautieria for others or, conversely, revision of the nomenclature of separate genus names for separate Ramaria clades will require the investigation of many taxa (e.g., Turbinellus and Gloeocantharellus ) along with Ramaria .…”
Section: Discussionmentioning
confidence: 99%
“…Description, discussion, drawings and photographs are provided. a problematic genus (e.g., Corner, 1969;González-Ávila et al, 2020, Ralaiveloarisoa et al, 2021. Linderomyces Singer and Gomphus sect.…”
Section: Introductionmentioning
confidence: 99%